Convention Center Universitas Muhammadiyah Surakarta - Sutrisno, Sutrisno; , Ronim Azizah, ST, MT; , Nur Rahmawati S, ST, MT (2015)
The quality of Human Resources (HR) largely rests one of them in the education sector and the development of the human person, especially to form akhlakulkarimah and morals. Islamic education becomes a vital necessity for the youth of Islam today. More and more young Muslims who do not know the nature of Islam itself as a living system. It happened because of the dichotomy between science of religion (Islamic) and science (Scientific) in the body of the Muslim education system itself. SurakaUniversitas Muhammadiyah Surakarta is one of the best private universities in Indonesia with berbgai prestasi.Secara institutions Surakarta Muhammadiyah University gained the confidence to open new Double Degree program at Charles Darwin University, Australia for the Department of Management and Derby University, England. 2014 University of Muhammadiyah Surakarta opened Joint Degree with Kyungdon University, Korea to Study Program in Civil Engineering, Mechanical Engineering, Information Technology, Economics and Management. By National Taiwan University of Science & Technology (NTUST) and National Taipei University of Technology (ntut) Taiwan's Civil Engineering Program (S1 and S2), Architectural Engineering, Mechanical Engineering (S1 and S2), as well as the Management and Economics Accounting (S1 and S2). Universitas Muhammadiyah Surakarta opened 3 new Twinning Program, namely Psychology - ECD, Law - Civics, and Geography Education - Geography, and 2 vocational program, namely the 3-D animation and Islamic Banking. (Guidelines for Academic Year 2014/2015). The continued development of a university, it is necessary to support facilities to accommodate the various activities at the University of Muhammadiyah Surakarta. Supporting facilities that did not exist at the Muhammadiyah University of Surakarta one multi-purpose building. Currently the graduation ceremony at the University of Muhammadiyah Surakarta still use sports hall / GOR as the container of the graduation ceremony. If the terms of the function of the sports hall is a building that functioned as a container of activities associated with sports such as volleyball, basketball, martial arts, etc., so that the need for support facilities to accommodate the graduation ceremony at the University of Muhammadiyah Surakarta. During the graduation ceremony of the University of Muhammadiyah Surakarta still disrupt lectures, especially on campus II, so it is often closed.